Fear of Being Black in America - Adriana Barešić ([sic])
The Fire This Time, written and edited by Jesmyn Ward, is a collection of various essays, poems, and stories. It is written by different authors who describe their experiences of being black in America. The title of the book is a reference to James Baldwin's work The Fire Next Time, published about fifty years prior to this book, since it discusses the same themes of race and identity but in a more contemporary context and through voices of various authors.The authors wrote the book in relation to all the historical events that led to the current position of black people in America while also describing their own experiences and reactions to the more contemporary events of police brutality and the Black Lives Matter movement. As Jasmyn Ward states in her introduction: “… the past is in the present, how heavily the past bears on the future; we cannot talk about black lives mattering without reckoning with the very foundation of this country,” (9) so have these essayists and poets reflected upon past, from speaking of the American Civil War, The Reconstruction Era to Great Migration and The Civil Rights Movement of the 1960s; all the while describing their memories of the first time they had realized they were black, in a social and cultural sense, as well as the first time they had seen how cruel the world could be towards those who are "different." Some of them, such as Wendy S. Walters, went deeper into research rather than reaching for their own experiences; thus exploring the evidence of inhumane treatment of dead black slaves while looking into the specifically assigned graveyards in New Hampshire.